BMI as a Predictor for Perioperative Outcome of Laparoscopic Colorectal Surgery: a Pooled Analysis of Comparative Studies. Issue 4 (April 2017) - He, Yazhou; Wang, Jiarong; Bian, He; Deng, Xiangbing; Wang, Ziqiang
Abstract : BACKGROUND: There has been a long-lasting controversy about whether higher BMI is associated with worse perioperative outcomes of laparoscopic colorectal surgery. Recently, a number of newly published investigations have made it possible to draw a quantitative conclusion. OBJECTIVE: We conducted this comprehensive meta-analysis to clarify the exact effect that BMI imposes on perioperative outcome of laparoscopic colorectal surgery. DATA SOURCES: We systematically searched MEDLINE, Embase, and Cochrane Library databases to identify all relevant studies. STUDY SELECTION: Comparative studies in English that investigated perioperative outcome of laparoscopic colorectal surgery for patients with different BMIs were included. Quality of studies was evaluated by using the Newcastle-Ottawa Scale. INTERVENTION: The risk factor of interest was BMI. MAIN OUTCOME MEASURES: Effective sizes were pooled under a random-effects model to evaluate preoperative, intraoperative, and postoperative outcomes. RESULTS: A total of 43 studies were included. We found that higher BMI was associated with significantly longer operative time ( p < 0.001), greater blood loss ( p = 0.01), and higher incidence of conversion to open surgery ( p < 0.001). Moreover, BMI was a risk factor for overall complication rates ( p < 0.001), especially for ileus ( p = 0.02) and events of the urinary system ( p = 0.03). Significant association was identified between higher BMI and risk of surgical site infection ( p < 0.001) and anastomotic leakage ( p = 0.02). Higher BMI might also led to a reduced number of harvest lymph nodes for patients with colorectal cancer ( p = 0.02). The heterogeneity test identified no significant cross-study heterogeneity, and the results of cumulative meta-analysis, sensitivity analysis, and the publication bias test verified the reliability of our study. LIMITATIONS: Most studies included were retrospectively designed. CONCLUSIONS: Body mass index is a practical and valuable measurement for the prediction of the perioperative outcome of laparoscopic colorectal surgery. Higher BMI is associated with worse perioperative outcome. More accurate conclusions, with more precise cutoff values, can be achieved by future well-designed prospective investigations.